Redescription of Microspio moorei (Gravier, 1911) (Annelida: Spionidae) with inclusion of a taxonomic key for all the species of the genus - Fonseca-González, Idalyd; Londoño-Mesa, Mario H.; Delgado-Blas, Víctor H. (Zootaxa, 2022)
Microspio moorei (Gravier, 1911), described from Admiralty Bay, King George Island (Antarctic Peninsula), has not been recorded since the original description, based on a single specimen, the holotype. Thus, subsequent comments and observations about the species have been made based only on the original description and with no information on morphological variations of the species. A re-description of this species is presented based on new material collected from a bay near the type locality, with detailed descriptions and illustrations of morphological characters. A key to all species of Microspio Mesnil, 1896 is provided. This research was part of the Colombian Antarctic Program, in collaboration with the Chilean Antarctic Institute (INACH).